Implementasi Strategi KADIN Kota Bandung dalam Mempersiapkan UMKM Menuju Pasar Ekspor - Aurreta Jasmine Mahardani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the implementation of strategies by the Bandung Chamber of Commerce and Industry (KADIN) in preparing micro, small, and medium enterprises (MSMEs) to enter export markets as a local Trade Promotion Organization (TPO). Using a qualitative approach with a single case study design, data were collected through in-depth interviews, observations, and documentation. The findings indicate that KADIN Bandung has translated export promotion instruments into five capacity-building stages: socialization, product curation, standardization, consultation, and business matching. However, a “natural selection” or drastic attrition phenomenon was identified, where only approximately 10% of MSMEs successfully reached the real export stage and only 20% consistently utilized digital platforms. Analysis using the Edwards III model reveals that strategic effectiveness is hindered by passive communication patterns, limited independent resources, gaps in MSME disposition, and suboptimal cross-institutional bureaucratic coordination. The novelty of this study lies in dissecting the attrition mechanism within the coaching pipeline of a local-level TPO, emphasizing the need for strategic reorientation toward proactive communication and a strengthened, integrated support ecosystem.